Knowledge Transfer and Entrepreneurial Interest in the Perspective of Informal Economic Education in Urban Farming Family Business - Muhammad Hasan; Citra Ayni Kamaruddin; Nurdiana Nurdiana; Nurjannah Nurjannah; Nur Arisah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The role of entrepreneurship in a country's economy, especially in poverty alleviation and employment, needs to be supported by economic education that takes place in the family. This study aims to explore the informal economy education process of knowledge transfer and its relation to entrepreneurial interest. This research is a research with a qualitative approach with the unit of analysis in the urban farmer family business. Informants from this research are children or the next generation in urban farming family businesses. The determination of informants in this study was carried out with certain considerations in accordance with the research objectives. Data collection techniques used are interviews and observations. The data analysis technique used in this study is a qualitative data analysis technique using the Miles and Huberman model. The findings of this study indicate that informal economic education which is implemented through knowledge transfer within the family is carried out by directly involving children as successors in business activities. Parents as the previous generation transfer knowledge verbally and provide examples to successors. The successor receives and absorbs the knowledge given by the predecessor and then applies that knowledge in running the business. The successor applies the knowledge provided by the predecessor by adding creativity and innovation.